2019
DOI: 10.1128/msphere.00216-19
|View full text |Cite
|
Sign up to set email alerts
|

Jet-Setting Koalas Spread Cryptococcus gattii VGII in Australia

Abstract: Cryptococcus gattii molecular type VGII is one of the etiologic agents of cryptococcosis, a systemic mycosis affecting a wide range of host species. Koalas (Phascolarctos cinereus) exhibit a comparatively high prevalence of cryptococcosis (clinical and subclinical) and nasal colonization, particularly in captivity. In Australia, disease associated with C. gattii VGII is typically confined to Western Australia and the Northern Territory (with sporadic cases reported in eastern Australia), occupying an enigmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…2011, Schmertmann et al . 2019). Similarly, disproportionately large number of abdominal cryptococcosis in the current study where observed in patients domiciled in Perth, Western Australia compared to the Eastern states and South Australia suggesting that the alimentary tract might be more likely to be the primary portal of entry for such biotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2011, Schmertmann et al . 2019). Similarly, disproportionately large number of abdominal cryptococcosis in the current study where observed in patients domiciled in Perth, Western Australia compared to the Eastern states and South Australia suggesting that the alimentary tract might be more likely to be the primary portal of entry for such biotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information regarding treatment and outcome was not provided in either of these studies. Previously California and Western Australia have been noted to have a high overall prevalence of C. gattii VGII and VGIII (Byrnes 3rd et al 2011) associated with climatic conditions, soil types, and the diversity of eucalyptus (WA only) and other native trees (McGill et al 2008, Carriconde et al 2011, Schmertmann et al 2019. Similarly, disproportionately large number of abdominal cryptococcosis in the current study where observed in patients domiciled in Perth, Western Australia compared to the Eastern states and South Australia suggesting that the alimentary tract might be more likely to be the primary portal of entry for such biotypes.…”
Section: Discussionmentioning
confidence: 99%
“…42 Key Australian papers on C. gattii infection include a comprehensive review by Chen et al, 6 insights derived from a nationwide retrospective study of culture-confirmed C. gattii from 2000 to 2007 14,25 and work emphasising its zoonotic aspects. 43,44 There has been no prospective treatment study focused on C. gattii infection to date and no new data have emerged to guide therapy of C. gattii infection since the previous 2014 guidelines. Locally, clinicians typically use a prolonged induction phase with amphotericin B and 5-flucytosine for 4-6 weeks followed by consolidation therapy for 12-18 months, for treatment of CNS cryptococcosis.…”
Section: Treatment Of C Gattii Infectionmentioning
confidence: 99%
“…One final note: Western Australia is the region of the continent most prone to tsunamis (55), and it is becoming apparent that at least some populations of Australian C. gattii originated in the western region (i.e., Perth) and have been anthropogenically transported via infected animals (i.e., koalas) to other parts of the continent (56). A tsunami-borne mechanism of transport from ocean to land in Western Australia is highly speculative but certainly possible if the coastal waters were previously contaminated.…”
Section: Pathogen Dispersal and Black Swansmentioning
confidence: 99%